Habitat complexity affects benthic harmful dinoflagellate assemblages in the fringing reef of Rawa Island, Malaysia - Yong, Hwa Lin; Mustapa, Nurin Izzati; Lee, Li Keat; Lim, Zhen Fei; Tan, Toh Hii; Usup, Gires; Gu, Haifeng; Litaker, R. Wayne; Tester, Patricia A.; Lim, Po Teen; Leaw, Chui Pin (Elsevier, 2018)
Few studies have investigated the effect of fine-scale habitat differences on the dynamics of benthic harmful dinoflagellate assemblages. To determine how these microhabitat differences affect the distribution and abundance of the major benthic harmful dinoflagellate genera in a tropical coral reef ecosystem, a field study was undertaken between April–September 2015 and January 2016 on the shallow reef flat of the fringing reef of Rawa Island, Terengganu, Malaysia. Sampling of benthic dinoflagellates was carried out using an artificial substrate sampling method (fiberglass screens). Benthic microhabitats surrounding the sampling screens were characterized simultaneously from photographs of a 0.25-m2 quadrat based on categories of bottom substrate types. Five taxonomic groups of benthic dinoflagellates, Ostreopsis, Gambierdiscus, Prorocentrum, Amphidinium, and Coolia were identified, and cells were enumerated using a light microscope. The results showed Gambierdiscus was less abundant than other genera throughout the study period, with maximum abundance of 1.2 × 103 cells 100 cm−2. While most taxa were present on reefs with high coral cover, higher cell abundances were observed in reefs with high turf algal cover and coral rubble, with the exception of Ostreopsis, where the abundance reached a maximum of 3.4 × 104 cells 100 cm−2 in habitats with high coral cover. Microhabitat heterogeneity was identified as a key factor governing the benthic harmful dinoflagellate assemblages and may account for much of the observed variability in dominant taxa. This finding has significant implications for the role of variability in the benthic harmful algal bloom (BHAB) outbreaks and the potential in identifying BHAB-related toxin transfer pathways and the key vectors in the food webs.